Government Policies and Corporate Social Responsibility: Analyzing the Influence on Organizational Practices and Stakeholder Perceptions - Usmany, Paul (International Journal of Business, Law, and Education, 2024)
This study investigates the influence of government policies on corporate social responsibility (CSR) practices and stakeholder perceptions. Utilizing a mixed-methods approach, the research combines quantitative data from surveys of 350 companies across various industries with qualitative insights from in-depth interviews and case studies. The findings reveal that mandatory regulations significantly drive CSR engagement, while financial incentives encourage voluntary CSR efforts. Stakeholder perceptions are more favorable towards CSR initiatives perceived as authentic and aligned with their values. Additionally, the impact of government policies on CSR varies across different industries and regions, emphasizing the importance of context-specific strategies. The study offers valuable insights for policymakers and business leaders on designing effective regulatory and financial tools to promote genuine and impactful CSR practices.